Curriculum development in language teaching - Jack C. Richards (New York : Cambridge University Press, 2001)
This book seeks to describe and examine the process of curriculum development in language teaching in order to acquaint language teachers and teachers-in-training with fundamental issues and practices in language curricular development.
Chapter1. The origins of language curriculum development -- Chapter2. From syllabus design to curriculum development -- Chapter3. Need analysis -- Chapter4. Situation analysis -- Chapter5. Planning goals and learning outcomes -- Chapter6. Course planning and syllabus design -- Chapter7. Providing for effective teaching -- Chapter8. The role and design of instructional materials -- Chapter9. Approaches to evaluation .
Includes bibliographical references and index.
Keywords: ENGLISH LANGUAGE STUDY AND TEACHING